Natural Products Against Renal Fibrosis via Modulation of SUMOylation - Liu, Peng; Zhang, Jing; Wang, Yun; Wang, Chen; Qiu, Xinping; Chen, Dan-Qian (Frontiers in Pharmacology, 2022)
Renal fibrosis is the common and final pathological process of kidney diseases. As a dynamic and reversible post-translational modification, SUMOylation and deSUMOylation of transcriptional factors and key mediators significantly affect the development of renal fibrosis. Recent advances suggest that SUMOylation functions as the promising intervening target against renal fibrosis, and natural products prevent renal fibrosis via modulating SUMOylation. Here, we introduce the mechanism of SUMOylation in renal fibrosis and therapeutic effects of natural products. This process starts by summarizing the key mediators and enzymes during SUMOylation and deSUMOylation and its regulation role in transcriptional factors and key mediators in renal fibrosis, then linking the mechanism findings of SUMOylation and natural products to develop novel therapeutic candidates for treating renal fibrosis, and concludes by commenting on promising therapeutic targets and candidate natural products in renal fibrosis via modulating SUMOylation, which highlights modulating SUMOylation as a promising strategy for natural products against renal fibrosis.